Research on the FRP bridge girder under static load - Poneta, Paweł; Siwowski, Tomasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The CFRP composite materials due to their excellent mechanical properties are more and more often used in civil engineering. In recent more than ten years one could have observed f.e. much more wider application of FRP in bridge construction. The main goal of the ongoing research project was to develop and demonstrate FRP composite bridge girder, including their technical design, material research, manufacturing technique selection and structural testing on full scale model. The objective of the paper is the development and research on a new FRP bridge girder fabricated by VARTM manufacturing technique. The reduced scale prototype girder with the total length of 13,5 m was tested to evaluate its carrying capacity, overall behavior under ultimate static load, as well as modes of failure. The girder met the prescribed serviceability and safety criteria and is likely to be implemented on-site soon for bridge construction. The output of the research project gives a very promising future for the FRP application in bridge engineering.